Adsorptive stripping voltammetric determination of venlafaxine in urine with a mercury film microelectrode - Morais, Simone (2003)
An adsorptive stripping voltammetric procedure for the determination of the antidepressant venlafaxine in urine using a mercury film microelectrode wasdeveloped. The method is based on controlled adsorptive accumulation of the drug at the potential of 1.00V (vs. Ag/AgCl) in the presence of 1.25 x10 -2 molL- 1 borate buffer (pH 8.7). Urine samples were analyzed directly after performing a ten-fold dilution with the supporting electrolyte but without other pretreatment. The limit of detection obtained for a 30 s collection time was 0.693x 10- 6 mol L -1. Recovery experimentsgave good results at the 10 -6 mol L- 1 level (bias less 5% were obtained).